1984
DOI: 10.1111/j.1755-3768.1984.tb03062.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Anterior Uveitis and Hla Antigens

Abstract: Different clinical entities of acute anterior uveitis (AAU) may occur due to different pathogenetic, race and geographig conditions. A highly significant association of HLA‐B27 with AAU has been confirmed in different countries. HLA‐B27 associated AAU was associated neither with MLC (HLA‐D) determinants nor with α1‐antitrypsin phenotype MZ. Family studies suggested that a pleiotropic HLA‐B27 linked gene with autosomal dominant inheritance, incomplete penetrance and variable expressivity may determine the susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…AAU can be associated with inflammation elsewhere in the body [ 1 , 2 ]. A number of studies have shown a strong association of HLA-B27 antigen associated anterior uveitis with systemic, especially autoimmune diseases, of which ankylosing spondylitis is the most common, which was also confirmed in our study [ 4 , 7 , 10 , 16 , 18 , 19 ]. A significantly greater proportion of HLA-B27+ (more than half) than HLA-B27− patients (less then quarter) had associated systemic disease, which was in accordance with previous studies [ 4 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…AAU can be associated with inflammation elsewhere in the body [ 1 , 2 ]. A number of studies have shown a strong association of HLA-B27 antigen associated anterior uveitis with systemic, especially autoimmune diseases, of which ankylosing spondylitis is the most common, which was also confirmed in our study [ 4 , 7 , 10 , 16 , 18 , 19 ]. A significantly greater proportion of HLA-B27+ (more than half) than HLA-B27− patients (less then quarter) had associated systemic disease, which was in accordance with previous studies [ 4 ].…”
Section: Discussionsupporting
confidence: 89%
“…Multiple reports have shown that the clinical features of HLA-B27+ and − AAU differ significantly [ 3 , 7 , 9 , 10 , 12 , 16 , 18 ]. In our case, the differences between the two groups were also noticeable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation